Trade adjustment in the European Union - a structural estimation approach - Vesna Corbo; Chiara Osbat (European Central Bank (ECB), 2013)
We estimate the elasticity of substitution of a country's imports, and that of its exports on the world market, for EU countries using sector level trade data. We present a new empirical strategy based on the identification scheme by Feenstra (1994), which enables the estimation of elasticities from data on exports. Moreover, our use of bootstrap methods allows us to obtain better elasticity measures, and to better characterize their accuracy. Our results show much heterogeneity in the estimates of the elasticity of substitution across industrial sectors. This, in turn, points to heterogeneity across countries, due to different production and trade structures. We obtain aggregate elasticities for the EU27 countries, with a mean of 3.5 for imports and 4.0 for exports, bringing us closer to traditional estimates and bridging the gap between the newer micro data estimates and the more traditional estimates found in the macroeconomic literature.
Keywords: C23; F14; F47; 330; Aggregation; calibration of macroeconomic models; Elasticity of Substitution; heterogeneity